PERBANDINGAN NILAI KEKERASAN PERMUKAAN ENAMEL PADA PERENDAMAN OBAT KUMUR CENGKEH DENGAN DAN TANPA PENAMBAHAN SALIVA BUATAN - Lindawati, Yumi; Novia, Novia (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2016)
Nowadays herbal mouthwash is widely consumed by the society, one of which is mouthwash containing cloves. Cloves contain minerals such as calcium and phosphorus which can help the remineralization of enamel. Mouthwash containing clove oil has antibacterial, antimicrobial effects, and can inhibit decalcification of enamel. The purpose of this study was to investigate the effect of immersion in clove mouthwash and the effect of of immersion in clove mouthwash with addition of artificial saliva on the hardness of enamel surface after immersion in commercial orange juice. It was a laboratory experimental pre-posttest control group design. Thirty two permanent maxillary first premolar extracted for orthodontic reason which qualify inclusion and exclusion criteria were used in this study. All samples were immersed in commercial orange juice for 5 minutes for demineralization then they were divided into group of clove mouthwash immersion without addition of artificial saliva and group of clove mouthwash immersion with addition of artificial. The surface enamel hardness before immersion, after immersed in commercial orange juice and after immersed in clove mouthwash of each sample was measured using Microvickers Hardness Tester FM-800. The results of the research that has been tested with Paired T-Test showed a significant decrease (p<0,05) of surface enamel hardness in clove mouthwash immersion without addition of artificial saliva group, while the group of clove mouthwash immersion with addition of artificial saliva showed a significant increase (p<0,05) of surface enamel hardness. The conclusion of this research showed that the value of enamel hardness is higher with the addition of artificial saliva than without addition of artificial saliva in clove mouthwash.